Unpacking Anti-Bullying Discourse: Beyond Binaries of Safety and Danger / Queer Kids and Social Violence: The Limits of Bullying - Lee, Hayoung (Journal of Childhood Studies)

(untitled) (Canadian Association for Young Children, 2026)
This book review discusses Queer Kids and Social Violence: The Limits of Bullying, edited by Elizabethe Payne and Melissa J. Smith, which unpacks the anti-bullying framework that depoliticizes and individualizes LGBTQ+ youth in schools. Thirteen chapters with different methodologies and critical perspectives on social violence against queer youth focus on better understanding the experiences of queer and trans youth and disrupt the simplistic and individualized intervention to create “safe space” in schools. The book emphasizes how bullying is a structural mechanism through which gender privilege is (re)produced in different forms, by different agents, and in different directions within schools.